2016
DOI: 10.1002/jbm.a.35707
|View full text |Cite
|
Sign up to set email alerts
|

Nanoporous metals for biodegradable implants: Initial bone mesenchymal stem cell adhesion and degradation behavior

Abstract: Nanostructured Fe-Mn and Fe-Mn-Zn metal scaffolds were generated through a well-controlled selective leaching process in order to fulfill the growing demand for adjustable degradation rates and improved cellular response of resorbable materials. Mouse bone marrow mesenchymal stem cells (D1 ORL UVA) were seeded onto eleven, carefully chosen nanoporous surfaces for 24 h in vitro. Using a combination of fluorescence microscopy, scanning electron microscopy (SEM), and an MTS assay, it was discovered that scaffolds… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 58 publications
0
10
0
Order By: Relevance
“…Substantial variability in the thickness of the corrosion layer was noted around the implants, and resorption appeared slower than expected in comparison to previous in vitro study demonstrating a corrosion rate of 0.0905 mm/year for Fe30Mn immersed in phosphate-buffered saline. 16 It has been demonstrated that corrosion rates vary substantially depending on anatomical locations and species, and on local differences such as blood flow, protein content, pH and temperature. 3,4,6,7,13,21 The in vivo resorption rate of Fe30Mn was not determined in this study as the resorption of Fe30Mn wires was not apparent radiographically, and the residual core wire and corrosion layer could not be consistently differentiated on histological sections.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Substantial variability in the thickness of the corrosion layer was noted around the implants, and resorption appeared slower than expected in comparison to previous in vitro study demonstrating a corrosion rate of 0.0905 mm/year for Fe30Mn immersed in phosphate-buffered saline. 16 It has been demonstrated that corrosion rates vary substantially depending on anatomical locations and species, and on local differences such as blood flow, protein content, pH and temperature. 3,4,6,7,13,21 The in vivo resorption rate of Fe30Mn was not determined in this study as the resorption of Fe30Mn wires was not apparent radiographically, and the residual core wire and corrosion layer could not be consistently differentiated on histological sections.…”
Section: Discussionmentioning
confidence: 99%
“…9,12,14 In this context, recent in vitro and in vivo studies investigated different compositions of iron-manganese alloys with intermediate degradation rate compared with pure iron and magnesium alloys, that may carry a greater potential for temporary internal fixation during fracture healing. 10,11,15,16 Iron-manganese alloy containing 35 wt% manganese 9 was found to have magnetic and mechanical properties close to 316L stainless steel (SS), 17 adequate ductility, and an in vitro corrosion rate three times higher than pure iron. 9,14,15 The purpose of this study was to evaluate the biodegradability and biocompatibility of an iron and manganese alloy containing 30 wt% manganese and 70 wt% iron (Fe30Mn) in bone in an in vivo rat model.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…Constructing an implant that will provide both adequate mechanical support upon implantation and degrade quickly enough to transfer the load to surrounding tissue is difficult, but one promising solution is to use metal scaffolds with significant porosity. Heidan and colleagues saw increased cell attachment on the nanoporous surfaces of a dealloyed Fe-Mn scaffold and measured an improved degradation rate due to the increased surface area for medium attack [ 55 ]. AM has already been demonstrated as an effective process for printing customized implants [ 56 ] and incorporating dealloying into the production process will enable the production of nanoporous and nanocomposite biomedical implants with the necessary material properties to improve performance and patient outcomes.…”
Section: Dealloyingmentioning
confidence: 99%
“…14,15 Besides, the scaffold material should have biodegradable matched with tissue growth in vivo. 16,17 Furthermore, the scaffolds should provide robust mechanical properties to avert bursting and leaking by themselves during implantation, 18 as well as to withstand blood pressure after implantation. Although vascular scaffolds, such as expanded polytetrafluoroethylene (ePTFE) and Dacron, have been successfully used in clinical practice.…”
Section: Introductionmentioning
confidence: 99%